2019
DOI: 10.3390/educsci9020099
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Applications in Education: Teachers Point of View

Abstract: A common conclusion of several studies is that augmented reality (AR) applications can enhance the learning process, learning motivation and effectiveness. Despite the positive results, more research is necessary. The current work aims to study the degree of diffusion of AR technology and teachers’ opinion about the need for continuous training, the process of creating 3D models, and the feasibility of AR applications development by teachers and students in school settings. Teachers are the common element in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 30 publications
6
76
0
11
Order By: Relevance
“…The modern approaches in teaching methodologies, based on the literature (theoretical and bibliographic) of recent decades [73][74][75] and in already published (new) researches and reviews in education [42,43,[76][77][78][79], as well as the field of media studies [40,[80][81][82][83], are:…”
Section: Teaching Methodologies Employing Audiovisual Media Technologiesmentioning
confidence: 99%
“…The modern approaches in teaching methodologies, based on the literature (theoretical and bibliographic) of recent decades [73][74][75] and in already published (new) researches and reviews in education [42,43,[76][77][78][79], as well as the field of media studies [40,[80][81][82][83], are:…”
Section: Teaching Methodologies Employing Audiovisual Media Technologiesmentioning
confidence: 99%
“…A pesar de que la heterogeneidad del modelo no es plena, la significancia del modelo es óptima, y nos ha permitido establecer acercamiento óptimo hacia la idea que se pretendió inferir con el planteamiento de este trabajo: la aplicación de Realidad Aumentada en las aulas provoca una mejora motivacional en el estudiantado. Este resultado torna en consonancia de los resultados expresados en investigaciones previas (Cabero & Roig, 2019;Tzima, Styliaras & Bassounas, 2019). De esta misma manera, la inferencia extraída de este estudio también guarda relación con los resultados de las revisiones sistemáticas referenciadas anteriormente, lo cual aporta consistencia al argumento que pretende dar este trabajo (Pellas, Fotaris, Kazanidis & Wells, 2019;Quintero, Baldiris, Rubira, Cerón & Vélez, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…Además, investigaciones llevadas a cabo como la de Di Serio et al (2013) demuestran cómo el uso de la Realidad Aumentada supone un aumento de la motivación que revierte en mayores niveles de satisfacción personal del alumnado y mayor atención, siempre y cuando las temáticas sean del interés de los mismos. En esta misma línea, estudios distinguidos a estudiantes de Educación Superior afirman que la aplicación de la Realidad Aumentada promueve una mejora motivacional, no solamente a futuros maestros, sino a futuros profesionales de distintas disciplinas, lo cual constata el carácter global de la Realidad Aumentada (Cabero & Roig, 2019;Tzima, Styliaras, & Bassounas, 2019;Fuchsova, & Korenova, 2019).…”
Section: Introducción Y Estado De La Cuestiónunclassified
“…Radu mentions that this problem is generated because AR is a relatively new technology in the classroom, and so only some students and teachers know how it works. For example, the article by Tzima [44] shows that AR is not well-known by students, and teachers who have used it found that its implementation is difficult when creating 3D content. Generally, the creation of these models is done by scholars.…”
Section: Why Consider Ar For Ch Education?mentioning
confidence: 99%
“…However, as described in the article by Wu [45], teachers can modify content in a simplistic way. Meanwhile, Tzima's [44] article develops a study about the effectiveness of applying AR in education by taking into account teachers' points of view. They claimed that employing AR is not advisable because many applications that currently exist not only often require some kind of payment, but they also undergo constant change.…”
Section: Why Consider Ar For Ch Education?mentioning
confidence: 99%